Metabolic syndrome among the inhabitants of the island of Vis - Missoni, Saša (Array, 2009)
Abstract: Metabolic syndrome (MS) was measured on the sample of 307 inhabitants of the island of Vis. Two criteria where used, one defined by the WHO (World Health Organization) and the other defined by the NCEP (National Cholesterol Education Program). The results according to NCEP definition showed a 47.2% of prevalence of MS, which is high but expected because of high independent factors analyzed in the study. These values are the highest in Croatia and among the highest measured in the World. MS definition according to NCEP proved to be more sensitive than that of the WHO, which shoved values of 21.2%. A link between MS (NCEP) and diabetes and cardiovascular diseases was also established